(untitled) (AmS-Skrifter, 2020)
Friend or foe? Trader or pirate? Commercial shipping along the archipelago of southern Norway in the early fifteenth century could be a risky business. Hanseatic skippers must have had detailed knowledge of sailing routes and good harbours along the route past Lindesnes towards Bergen. Among a chain of good natural harbours, Skjernesund near Mandal formed a hub, a protected inner route consisting of several good harbour areas sheltered from the exposed Skagerrak north of Skjernøya. An overview of dated shipwrecks along the coast of southern Norway is presented and their context discussed in relation to why they wrecked. It is striking that the majority of wrecks have been found in port areas. The most common interpretation of these wrecks individually is that there are natural explanations for these as losses at sea. By comparing the written sources and historical events from the main period of these shipwrecks, it is probable that in many cases the cause was piracy.